Analisis Tindak Pidana Penipuan Online dalam Konteks Hukum Pidana Cara Menanggulangi dan Pencegahannya - Simanungkalit, Jason Aaron Riado; Hertadi, Raihan; Hosnah, Asmak ul (Perhimpunan Sarjana Ekonomi dan Bisnis, 2024)
Fraud has been around for more than twenty centuries. The world continues to grapple with the devastating impact of financial crime. In this digital age, financial fraud is more sophisticated than ever. This article discusses the origins of fraud, its development, and technological advances in fraud prevention and security. In simple terms, fraud is deception with the intent to illegally gain financial advantage over a person or an entity. It refers to dishonest acts that deprive a person or entity of money or legal rights. Fraud requires the intentional misrepresentation of facts to convince someone to hand over money or property, unlike outright theft, which requires stealth or force. The crime of fraud is a form of crime that harms society financially and psychologically. This research aims to analyze various aspects related to fraud, including the motives of the perpetrators, the methods used, and the impact on victims and society. The impact of this crime is financially, emotionally, and psychologically detrimental to victims, and can undermine public trust in institutions and individuals. Through an in-depth understanding of the motives, methods, and impacts of fraud, this research contributes to the development of more effective prevention and law enforcement strategies. Preventive measures involving public education on the risks of fraud, increased legal awareness, and enhanced cooperation between law enforcement agencies and the private sector can be the first step in combating this phenomenon. In addition, strict and fair law enforcement against fraud perpetrators is also necessary to ensure justice for victims and minimize the possibility of similar crimes occurring in the future.